Kepastian Hukum Akta Jual Beli Tanah Di Bawah Tangan Yang Disahkan Oleh Notaris Di Kabupaten Sidenreng Rappang Provinsi Sulawesi Selatan - Rully, Jodie Angelia; Ismansyah, Ismansyah; Fendri, Azmi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Article 37 paragraph (1) PP No. 24 of 1997 concerning land registration, explains that the transfer of land rights can be carried out by transferring rights such as sale and purchase, exchange, gift, auction, inheritance, transfer of rights due to merger or consolidation and other transfers of rights. All transfers except auctions can only be registered if proven by a deed made by the Land Deed Official (PPAT). In the event that the land you wish to trade does not yet have a certificate, the process of transferring rights in accordance with the provisions of this Article cannot be carried out. Currently, many land buying and selling processes are carried out, not through PPAT, but buying and selling is done by deed under the hands of the parties. To strengthen the proof of private deeds, Article 1874 of the Civil Code regulates the ratification of private deeds as a form of strengthening private deeds by a notary. Therefore, the main problem is why the people in Sidenreng Rappang district choose to buy and sell land with a private deed legalized by a notary and what is the legal certainty of the private land sale and purchase deed that has been legalized by a notary. The sale and purchase of land using a private deed ratified by a notary is because the condition of the object of sale and purchase is not yet certified, buying and selling land using a private deed ratified by a notary is felt to be easier, faster and more affordable. Ratification by a notary of the private deed will guarantee that the parties really signed it, and that the private deed was indeed signed on that date.